Proteome Profiles of Digested Products of Commercial Meat Sources - Li, Li; Liu, Yuan; Zhou, Guanghong; Xu, Xinglian; Li, Chunbao (Frontiers in Nutrition, 2017)
This study was designed to characterize in vitro digested products of proteins from four commercial meat products, including dry-cured ham, cooked ham, emulsion-type sausage and dry-cured sausage. The samples were homogenized and incubated with pepsin and trypsin. The digestibility and particle sizes of digested products were measured. Nano LC-MS/MS was applied to characterize peptides. The results showed the highest digestibility and the lowest particle size in dry-cured ham (P<0.05), while the opposite was for cooked ham (P<0.05). Nano LC-MS/MS analysis revealed that dry-cured ham samples had the greatest number of 750-3500 Da Mw peptides in pepsin-digested products. In the digested products of cooked ham and emulsion–type sausage, a lot of peptides were matched with soy protein that was added in the formulations. In addition, protein oxidation was also observed in different meat products. Our findings give an insight into nutritional values of different meat products.